2013
DOI: 10.1055/s-0032-1326429
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to the development of cat scratch colon during colonoscopy

Abstract: Cat scratch colon (CSC) is an entity characterized by bright red linear tears which appear in the colonic mucosa during colonoscopy. Although they do not generally have clinical implications, cases of secondary pneumoperitoneum have been reported. To date, the prevalence, associated diseases, and factors that determine the appearance of CSC have not been adequately determined. We report a series of 20 cases of CSC found in 10715 consecutive colonoscopies. Demographic data, indication for the colonoscopy, endos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“… 6 These changes are edematous bowel wall and the presence of mucosal tears, the appearance of ‘cat scratch mucosa’. 15 17 , 86 No known specific laboratory markers have been discovered so far. Elevated erythrocyte sedimentation rate, mild anemia, and certain autoantibodies might be present.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“… 6 These changes are edematous bowel wall and the presence of mucosal tears, the appearance of ‘cat scratch mucosa’. 15 17 , 86 No known specific laboratory markers have been discovered so far. Elevated erythrocyte sedimentation rate, mild anemia, and certain autoantibodies might be present.…”
Section: Diagnosismentioning
confidence: 99%
“…Nevertheless, nonspecific macroscopic signs – such as mildly edematous, hyperemic bowel wall, and even ‘cat-scratch appearance’ on bowel mucosa – can also indicate underlying MC. 6 , 15 18 …”
Section: Introductionmentioning
confidence: 99%
“…Collagenous colitis (CC) is widely recognised as a cause of chronic diarrhoea. CC is sometimes diagnosed with cat scratch sign found during colonoscopy 1. On the other hand, no abnormality is observed in more than 80% of cases; hence, the diagnosis of CC cannot be made without biopsy.…”
Section: Descriptionmentioning
confidence: 99%
“…The lesions are not due to direct scope trauma. Recently, Baudet et al found CSC in 20 (0.19%) of the 10,715 colonoscopies in their series [3], finding collagenous colitis in 5 cases and diversion colitis in 15. Older age and male sex were significantly associated with CSC.…”
mentioning
confidence: 93%